2019
DOI: 10.1007/s10762-019-00608-x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of THz Beams: A “How to” Tutorial

Abstract: Attenuation of ultrashort THz pulses poses a significant technological challenge due to the broadband nature of such light pulses. Several methods exist for this purpose, including crossed wire grid polarizers, high refractive index, high resistivity silicon wafers, and ultrathin metal films. In this review, we discuss the operational principles of these methods, and highlight some of the advantages and potential pitfalls of the methods. We describe the limits of high-frequency operation of wire grid polarizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…wafers in the beam path [47]. In the collimated beam path the field strength is much lower than in the focus region, and we have confirmed that any nonlinear processes in the HR-Si wafers such as impact ionization [48] are undetectable.…”
Section: Experimental Setups For Nonlinear Single-pulse and Two-dimensupporting
confidence: 66%
“…wafers in the beam path [47]. In the collimated beam path the field strength is much lower than in the focus region, and we have confirmed that any nonlinear processes in the HR-Si wafers such as impact ionization [48] are undetectable.…”
Section: Experimental Setups For Nonlinear Single-pulse and Two-dimensupporting
confidence: 66%
“…1) also enables measurements on very thin sample substrates with which commercial setups usually end up with un-separable echo transients [6,27]. When the THz frequency increases, the silicon absorption becomes more noticeable and cannot be ignored [32,35] and frequency-dependent THz wave attenuation has also been reported when multiple high-resistivity Si plates were used as broadband THz attenuators [36]. Practically, with one single scan on bare substrate, the ratio T = |Ẽ (1st) sub /Ẽ (dir) sub | between the first echo and directly transmitted transients will count for all substrate relevant THz wave attenuation and give the amplitude correction term when comparing to (n sub -1) 2 /(n sub + 1) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This way, the electric field profile of the THz pulse can be measured. Figure 8a shows the THz pulse energy vs. the laser pulse energy (before frequency doubling), where the THz energy was before attenuation by the silicon wafer [36]. The experimental result shows that the maximum THz energy of 480 nJ can be obtained with the laser energy of 18.8 mJ, which leads to the THz field strength of 242 kV/cm.…”
Section: Experimental Results For Two-color-based Intense Thz Wave Generation Using the Laser Amplifiermentioning
confidence: 99%